2011
DOI: 10.1063/1.3646328
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon/hydrogen species incorporation on electronic structure of anatase-TiO2

Abstract: Articles you may be interested inThe electronic structure changes and the origin of the enhanced optical properties in N-doped anatase TiO2-A theoretical revisitResearch on the effect of crystal structures on W-TiO2 nanotube array photoelectrodes by theoretical and experimental methodsThe energy band structure and optical properties of C-doped and C/H-codoped anatase TiO 2 are investigated using the first-principles based on density-functional theory. The obtained results indicate that the structure of C/H-cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Our calculated band structure is in agreement with that of Li et al [23] in general. The impurity energy level below conduction band lies above Fermi level, so it is lack of electrons, and the one above valence band is blow Fermi level, then is occupied by electrons.…”
Section: Resultssupporting
confidence: 82%
“…Our calculated band structure is in agreement with that of Li et al [23] in general. The impurity energy level below conduction band lies above Fermi level, so it is lack of electrons, and the one above valence band is blow Fermi level, then is occupied by electrons.…”
Section: Resultssupporting
confidence: 82%
“…[3][4][5][6] A few latest researches show that different ions codoping into TiO 2 can further narrow its band gap and enhance its photocatalytic activity. [7][8][9][10][11][12][13][14] For instance, Jia et al studied the microscopic mechanism for band gap narrowing and the origin of the enhanced visible-light photocatalytic activity in N/S-codoped anatase TiO 2 . 7 Li et al reported the C/H-codoping produces significant band gap narrowing, which leads to higher visiblelight photocatalytic efficiency than the C-doped anatase TiO 2 .…”
mentioning
confidence: 99%
“…7 Li et al reported the C/H-codoping produces significant band gap narrowing, which leads to higher visiblelight photocatalytic efficiency than the C-doped anatase TiO 2 . 9 The research of Su et al suggested that the codoping of TiO 2 with N and Fe leads to the much narrowing of the band gap and greatly improves the photocatalytic activity under visible irradiation. 10 These results indicate that (co)doping is one of the most effective approaches to extend the absorption edge to the visible-light range in anatase TiO 2 .…”
mentioning
confidence: 99%
“…[3][4][5] A few latest researches show that different ions codoping into TiO 2 can further narrow its band gap and enhance its photocatalytic activity. [6][7][8][9][10][11][12][13] For example, Li et al reported the C/H-codoping produces significant bandgap narrowing, which leads to higher visible-light photocatalytic efficiency than the C-doped anatase TiO 2 . 8 The research of Su et al suggested that the codoping of TiO 2 with N and Fe leads to the much narrowing of the band gap and greatly improves the photocatalytic activity under visible-light irradiation.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] For example, Li et al reported the C/H-codoping produces significant bandgap narrowing, which leads to higher visible-light photocatalytic efficiency than the C-doped anatase TiO 2 . 8 The research of Su et al suggested that the codoping of TiO 2 with N and Fe leads to the much narrowing of the band gap and greatly improves the photocatalytic activity under visible-light irradiation. 9 These results indicate that codoping is one of the most effective approaches to extend the absorption edge to the visiblelight range in anatase TiO 2 .…”
mentioning
confidence: 99%